2014
DOI: 10.1210/jc.2013-3669
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Adversity Is Associated With Elevated Levels of Circulating Leptin, Irisin, and Decreased Levels of Adiponectin in Midlife Adults

Abstract: Early-life adversity is directly associated with elevated circulating leptin and irisin, and indirectly associated with elevated CRP and decreased adiponectin. These findings suggest that these adipomyokines may play a role in the pathogenesis of metabolic abnormality in a population with significant early life adversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 19 publications
0
48
0
2
Order By: Relevance
“…A possible explanation of these findings is illustrated in a recent study by Joung et al (2014) that demonstrated how childhood adversity can place stress on the endocrine system through the dysregulation of certain hormones (i.e. leptin, adiponectin and irisin) and the inflammatory marker Creactive protein (CRP) all of which have been associated with obesity and diabetes in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation of these findings is illustrated in a recent study by Joung et al (2014) that demonstrated how childhood adversity can place stress on the endocrine system through the dysregulation of certain hormones (i.e. leptin, adiponectin and irisin) and the inflammatory marker Creactive protein (CRP) all of which have been associated with obesity and diabetes in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…neglect, sexual and physical abuse) on disorders related to the endocrine system such as type 1 and type 2 diabetes mellitus, obesity, and metabolic diseases (Joung et al 2014; Thomas et al 2008;Widom et al 2012). A recent meta-analysis (Hemmingsson et al 2014) reported significant positive associations between the severity of childhood abuse and adult obesity.…”
mentioning
confidence: 99%
“…Ці-каві результати, що були отримані при вивченні да-них анкетування дорослих американців Kyoung Eun Joung і співавт. [8], які свідчать про те, що низька оцінка якості життя високоасоційована з розвитком абдомінального ожиріння і рівнем концентрації леп-тину, резистину, адипонектину в сироватці крові.…”
Section: резюме мета дослідження -визначення асоціації однонуклеотидunclassified
“…Indeed, stress-related hormones are able to affect the functioning of metabolic hormones (Joung et al, 2014) and MS on P8 from 4 to 12 h in mice leads to reductions of circulating glucose as well as leptin levels and increases in ghrelin levels early in life (Schmidt et al, 2006). Further pointing to a key modulating role of these metabolic hormones in the programming of the HPA axis; blocking the MS-induced ghrelin increase could reverse the MS effects on the HPA axis as well.…”
Section: Role Of Metabolic Hormones In Regulating the Hypothalamic-pimentioning
confidence: 99%